DNA Protective Effect of Mangosteen Xanthones: an in Vitro Study on Possible Mechanisms - Jing Lin; Yaoxiang Gao; Haiming Li; Lulu Zhang; Xican Li (Tabriz University of Medical Sciences, 2014)
Purpose: The aim of this study was to evaluate antioxidant ability of mangosteen shell and explore the non-enzymatic repair reaction and possible mechanism of xanthones in mangosteen shell. Methods: Mangosteen shell was extracted by methanol to obtain the extract of mangosteen shell. The extract was then determined by various antioxidant assays in vitro, including protection against DNA damage, •OH scavenging,DPPH• (1,1-diphenyl-2-picryl-hydrazl radical) scavenging, ABTS+• (2,2'-azino-bis(3-ethylbenzo- thiazoline-6-sulfonic acid diammonium) scavenging, Cu2+-chelating, Fe2+-chelating and Fe3+ reducing assays. Results: Mangosteen shell extract increased dose-dependently its percentages in all assays. Its IC50 values were calculated as 727.85±2.21,176.94±19.25, 453.91±6.47, 84.60±2.47, 6.81±0.28, 1.55±0.10, 3.93±0.17, and 9.52±0.53μg/mL, respectively for DNA damage assay, •OH scavenging assay, Fe2+-Chelating assay, Cu2+-Chelating assay, DPPH• scavenging assay, ABTS+• scavenging assay, Fe3+ reducing assay and Cu2+ reducing assay. Conclusion: On the mechanistic analysis, it can be concluded that mangosteen shell can effectively protect against hydroxyl-induced DNA oxidative damage. The protective effect can be attributed to the xanthones. One approach for xanthones to protect against hydroxyl-induced DNA oxidative damage may be ROS scavenging. ROS scavenging may be mediated via metal-chelating, and direct radical-scavenging which is through donating hydrogen atom (H·) and electron (e). However, both donating hydrogen atom (H·) and electron (e) can result in the oxidation of xanthone to stable quinone form.